Conservation of Native Flora and Fauna of Agro-Biodiversity Park in ANGRAU, Hyderabad, Andhra Pradesh, India - Khan, M. A. Aariff; Prabhavathi, K.; Krishna, A.; Rao, V. Vasudeva (International Journal of Bio-resource and Stress Management, 2014)
Deccan plateau region in India is unique due to presence of diversified geography and ecosystems with rich agricultural diversity including wild flora and fauna. However, it was over exploited by several anthropogenic activities. Acharya N.G. Ranga Agricultural University, Hyderabad has established first Agro-biodiversity Park in August, 2008 and is the first of its’ kind in India with a main objective of preserving, conserving and promoting the rich biodiversity of Deccan plateau region of Hyderabad. The park site is naturally spread with hillocks, boulders, undulated terrain with sloppy lands covered diverse vegetation besides a natural water tank. In the initial stage, the dangerous invasive alien species such as Parthenium hysterophorous, Lantana camera and Prosopis juliflora present in the vicinity were removed. Subsequently, several block plantations were developed with Teak and Mahua (70 %) and forest mixed tree species (30 %). Besides, separate generic blocks viz., palm and medicinal tree, mixed forest tree gardens and Ficus species diversity block were also developed. Of late, a rare, endemic, endangered and globally threatened species Ceropegia was identified in 2009. Since then, utmost care was taken for conservation in agro-biodiversity park. Water ponds and bodies were also created as a source of water for all resident and migratory bio-creatures for promotion of faunal genetic resources. At present, 24 species of insects, 5 species of fish and 8 species of reptiles were recorded. Out of 120 species of butterflies present in the Andhra Pradesh, 56 were found in this park.